Biopsychosocial Contributors to Metabolic Syndrome: A Secondary Analysis of 2007–2010 National Health and Nutrition Examination Survey Data. Issue 6 (November 2015) - Saylor, Jennifer; Friedmann, Erika
Abstract : Background: Metabolic syndrome (MetS) is a medical disorder that encompasses obesity, hypertension, dyslipidemia, and insulin resistance and increases the risk of type 2 diabetes, cardiovascular disease, and mortality. Objectives: A secondary data analysis was conducted using the National Health and Nutrition Examination Survey 2007–2010 data to evaluate the association of biopsychosocial factors with MetS among U.S. adults. Methods: Complex samples logistic regression models were used to estimate a parsimonious model, including contributions of biomedical, biosocial, and psychosocial factors to MetS. Results: According to the study's representative sample, more than 47 million Americans had MetS. Using the biopsychosocial model, the effects of biosocial and psychosocial variables, including education, smoking, low exercise, and depression, were independent predictors of MetS after controlling for the contributions of age, gender, and race. Discussion: There is a need for large-scale, longitudinal, and interventional studies to evaluate and alter these potential risk factors, thus reducing MetS.